Analysis of Environmental Applicability of HDPE Geomembrane by Simulated Applicability Testing for Waste Containment Construction - Jeon, Han-Yong (Frontiers in Materials, 2016)
Geosynthetic separation boxes made from recycled polymeric materials were designed to increase the waste landfill amount and develop the hydraulic performance in steep slope sides in the waste landfills. To evaluate the advantages of these geosynthetic separation boxes, index tests were conducted in order to compare the geonet composites and geosynthetic separation boxes. The tensile strength retention of the geosynthetic separation box plates exposed to UV light and leachate solutions was better than that of the geonet composites. The drainage performance of the geosynthetic separation boxes was compared with that of the geonet composites at a slope angle corresponding to a real waste landfill site. The drainage performance of the geosynthetic separation box plates was better than that of the geonet composites.